Creep Behaviour of Self-compacting Concrete Incorporating High Volume Fly Ash and its Effect on the Long-term Deflection of Reinforced Concrete Beam. (2017) - Kristiawan, Stefanus A.; Nugroho, Agung P.
Abstract: Sustainable infrastructures may be achieved by utilizing green construction materials. In term of reinforced concrete structure, this could be attained by the use of concrete with less cement content. In this research, self-compacting concrete has been developed with an inclusion of high volume fly ash as cement replacement. The benefit of incorporating high volume fly ash on the creep behavior self-compacting concrete was investigated through experimental laboratory. The short-term data were then used to estimate long-term creeps with the ACI 209 model. A computation of creep effect on the long-term deflection of reinforced self-compacting concrete beam was accomplished to study the influence of major parameters on the magnitude of deflection.